Analysis of raw cork production in Portugal and Catalonia using life cycle assessment - Dias, Ana Cláudia
Purpose: This study aims to (1) evaluate the environmental impacts associated with the three types of raw cork produced in Portuguese cork oak woodlands (in Alentejo region) considering two alternative practices for stand establishment (plantation and natural regeneration), (2) compare the environmental impacts of raw cork production in Portuguese cork oak woodlands and in Catalonian cork oak forests, and (3) assess the influence of different allocation criteria for partitioning the environmental impacts between the different types of raw cork produced.\nMethods: A cradle-to-gate approach was adopted starting with stand establishment up to cork storage in a field yard. The system boundaries include all management operations undertaken during the following stages: stand establishment, stand tending, cork stripping, and field recovery. The allocation of the environmental impacts to reproduction, second, and virgin cork was based on mass and market price criteria. An alternative allocation approach was simulated by allocating environmental impacts also to the wood produced in the cork oak stands. The impact assessment was performed using the characterization factors recommended by the International Reference Life Cycle Data System (ILCD).\nResults and discussion: In Portugal, cork produced from naturally regenerated stands has a better environmental performance than cork produced from planted stands, but the differences are smaller than 10 %. Different management models of cork oak stands in Portugal and Catalonia (agro-silvopastoral system and forest system, respectively) originate different impact levels, which tend to be significantly lower in Catalonia. The environmental hot spots in the two regions are also distinct. In Catalonia, they are associated with cleaning, road maintenance, and worker and cork transport. In Portugal, they are fertilization, pruning, and cleaning. The two allocation criteria affect significantly the results obtained for virgin cork in Portugal and for virgin and second cork in Catalonia. Besides, when impacts are also allocated to wood, mass allocation should be avoided as it would not create incentives for a sustainable management of cork oak stands.\nConclusions: The environmental impact from Catalonian cork may be reduced by decreasing mechanized shrub cleaning and road maintenance operations through the introduction of livestock in cork oak forests, and also by a better planning of management operations. For the Portuguese cork, improvements may be achieved by optimizing fertilizer dosage, planting nitrogen-fixing crops and pastures that improve soil quality, avoiding unnecessary operations, improving the efficiency of management operations, and increasing tree density.